2019
DOI: 10.1093/neuonc/noz244
|View full text |Cite
|
Sign up to set email alerts
|

Age and DNA methylation subgroup as potential independent risk factors for treatment stratification in children with atypical teratoid/rhabdoid tumors

Abstract: Abstract Background Controversy exists as to what may be defined as standard of care (including markers for stratification) for patients with atypical teratoid/rhabdoid tumors (ATRTs). The European Rhabdoid Registry (EU-RHAB) recruits uniformly treated patients and offers standardized genetic and DNA methylation analyses. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 29 publications
4
113
1
7
Order By: Relevance
“…Frequencies of germline mutations was taken from Frühwald et al [12]. Frequencies of ATRT-SMARCA4 is estimated based on studies published by Johann et al [22] and Frühwald et al [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequencies of germline mutations was taken from Frühwald et al [12]. Frequencies of ATRT-SMARCA4 is estimated based on studies published by Johann et al [22] and Frühwald et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of MRTs, pathogenic variants (hereafter “mutations”) affect the SMARCB1 gene. In rare cases (about 0.5–2% of ATRT [ 12 , 22 ]), SMARCA4 is mutated instead [ 17 , 42 , 43 ]. Since these mutations result in loss of the respective protein, loss of staining for either SMARCB1 or SMARCA4 by immunohistochemistry is used as a diagnostic tool to ensure the diagnosis of an ATRT [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncology Group ACNS0333 study, with some suggestion that ATRT-SHH benefit from high-dose chemotherapy approaches and ATRT-TYR benefit from radiotherapy [116,[118][119][120][121]. The EZH2 inhibitor tazemetostat is a rational approach to target the SWI/SNF complex and is being investigated in upcoming clinical trials; however, there is a paucity of early phase human data at the present time [122].…”
Section: Molecular Classification Of Pediatric Brain Tumors 257mentioning
confidence: 99%
“…Pinto et al have performed DNA-methylation profiling on their metachronous RT cases and reported that the CNS tumor cells often show methylation profiles distinct from those in extra-CNS tumor cells of the same patient (23). Data obtained by means of DNA methylation profiling are expected to further contribute to new valuable insights for a more profound understanding of molecular mechanisms of ATRTs and extra-CNS MRTs (9).…”
mentioning
confidence: 99%